Tubercular Osteomyelitis of Talus with Staphylococcal Co infection - Soraganvi, P; Ramakanth, R (Kathmandu University Medical Journal, 2015)
Tuberculosis osteomyelitis of foot bones is uncommon and may evade the diagnosis for long time because of atypical presentation, paucibacillary nature and relatively normal picture on laboratory investigations. As tuberculosis of bone mimic like chronic osteomyelitis, clinical picture with confection by other organism lead to misdiagnosis. A case of tubercular osteomyelitis of talus reported here for its rarity and atypical presentation. Clinical suspicion and histological confirmation of diagnosis is recommended avoiding undue delay and for early chemotherapy.Kathmandu University Medical Journal Vol.12(4) 2014; 298-300